Sympathetic Overdrive in Hypertension, The Role of Beta Blocker, Focus on Bisoprolol - Lucia Kris Dinarti (ACI (Acta Cardiologia Indonesiana), 2019)
Sympathetic neural factors played an important role in homeostatic blood pressure control. Dysregulation in sympathetic function may favor the development and progression of the hypertensive state. Beta-blocker, as one of antihypertensive drugs, provides several positive effects to hinder overactivity of sympathetic nerve in patients with hypertension.